Peran Perusahaan Daerah Air Minum Way Sekampung dalam Pemerataan Aksesibilitas Air Bersih di Kabupaten Pringsewu - Ulfa Umayasari; Syarief Makhya; Maulana Mukhlis; Tabah Maryanah (PERSPEKTIF, 2022)
This article aims to provide an analysis of the accessibility of the community to the clean water supply policy in Pringsewu Regency which is managed by the Regional Drinking Water Company. The problem is focused on the limited public access to clean water sourced from the Way Sekampung Regional Drinking Water Company, Pringsewu Regency which is only able to reach Gadingrejo and Pringsewu Districts. To approach this problem, a reference to the concept of accessibility is used (Hakim, 2010). The data were collected through interviews, documentation, and observation and analyzed qualitatively. This study concludes that the community's access to clean water which is managed by the Way Sekampung Water Supply Company in Pringsewu Regency tends not to reach all sub-districts in Pringsewu Regency. PDAM Way Sekampung is only able to access two sub-districts, namely Pringsewu District and Gadingrejo District, out of the total sub-districts in Pringsewu Regency, which amount to 9 (nine) sub-districts. The lack of equal access is due to several factors, including; The volume of water consumed by the community tends to be large, while the Way Sekampung Regional Water Company has limited raw water sources, different access to clean water, the time it takes to get clean water, the quality and price of clean water is not optimal, as well as local government policies in providing clean water that has not been maximized.